Factors Related to Tobacco Cessation Attempts Among Turkish Adolescents: A Structural Equation Model Analysis - Cemre Hilal Kesen Yurtcanli; Murat Tuğberk Bakar; Şükran Peker; Nadiye Pinar Ay (Thoracic Research and Practice)
Objective: The Turkish Global Youth Tobacco Survey (GYTS) 2017 revealed that 17.9% of students aged 13-15 used tobacco products and 7.7% smoked cigarettes. Given the high prevalence of smoking, it is important to evaluate the factors associated with quit attempts among adolescents. This study aimed to identify the factors associated with Turkish adolescents’ attempts to quit smoking using Structural Equation Model (SEM) analyses.